Conectividade hidrológica determinando a estrutura da metacomunidade de protozoários flagelados planctônicos em um sistema rio-planície de inundação Neotropical. - Lansac-Toha, Fernando Miranda (2015)
Species distribution patterns are regulated by a combination of abiotic factors, biotic interactions and dispersal processes. In aquatic environments, the dispersal potential of the organisms is directly related to the hydrological connectivity among habitats. In this study, we approach three types of environments of the Upper Paraná River-floodplain system, which differ in their degree of connectivity: lotic environments, connected lakes and isolated lakes. We aimed to investigate if the relative role of the environmental and spatial components in structuring the heterotrophic flagellates depends on the degree of hydrological connectivity. We expect that communities in isolated lakes would be more subject to dispersal limitation, while in connected lakes and lotic environments the communities would be regulated mainly by environmental variables (species sorting). We sampled in the planktonic region of 23 environments during the low water period in 2014. We determined the relative importance of the assembly mechanisms using variance partitioning and evaluated changes in beta diversity and environmental heterogeneity in each type of environment. The greater contribution of the environmental variables in structuring the hetrotrophic flagellates metacommunity, regardless of the hydrological connectivity, may be related to the elevated dispersal capacity of those microorganisms. The spatial component was also significant, however only in the isolated lakes, a species sorting mechanism partially constrained by dispersal limitation. In summary, our results support the idea that microorganism communities are mainly structured by environmental factors, even considering environments with distinct connectivity degree.